2023
DOI: 10.3390/antiox12051107
|View full text |Cite
|
Sign up to set email alerts
|

Non-Melanoma Skin Cancer and Vitamin D: The “Lost Sunlight” Paradox and the Oxidative Stress Explanation

Abstract: UV radiation (UVR) is responsible for inducing both harmful and beneficial effects on skin health. Specifically, it has been reported to disrupt oxidant and antioxidant levels, leading to oxidative stress conditions in skin tissue. This phenomenon might trigger photo-carcinogenesis, resulting in melanoma, NMSC (non-melanoma skin cancer), such as BCC (basal cell carcinoma) and SCC (squamous cell carcinoma), and actinic keratosis. On the other hand, UVR is essential for the production of adequate vitamin D level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Our findings highlight how free screening events have the capability to engage individuals who may not typically have access to dermatology clinics [ 2 ]. Dermatologists should seek to host these events in rural and underserved areas to target this demographic who often lack skin cancer screening [ 13 ]. It should be emphasized, however, that the coordination of proper follow-up with dermatology or a primary care provider if necessary should be prioritized at events in these areas due to the potential lack of local providers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight how free screening events have the capability to engage individuals who may not typically have access to dermatology clinics [ 2 ]. Dermatologists should seek to host these events in rural and underserved areas to target this demographic who often lack skin cancer screening [ 13 ]. It should be emphasized, however, that the coordination of proper follow-up with dermatology or a primary care provider if necessary should be prioritized at events in these areas due to the potential lack of local providers.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress [ 37 , 38 ] and microbiome parameters [ 39 ], although very important, would not be assessed, as it is very difficult and not practical to predict those parameters by assessing patients age, gender, comorbidities, and lifestyle choices.…”
Section: Methodsmentioning
confidence: 99%
“…Current research also suggests that nicotinamide plays a role in blocking inflammatory cell activation and influences cell life span, survival, and cancer progression [ 8 , 9 ]. Studies have reported that patients with a history of non-melanoma skin cancer often present with vitamin deficiencies; thus, it has been proposed that vitamin replacement can be of great importance in these patients [ 10 , 11 ]. The recommended dose of oral supplementation with nicotinamide is 500 mg twice daily [ 5 ].…”
Section: Introductionmentioning
confidence: 99%